NILAI-NILAI KEMANUSIAAN DALAM CERITA ANAK MINANGKABAU - Gayatri, Satya; Ariany, Ria; Lita, Ratni Prima; Isramirawati, Isramirawati (Diksi, 2021)
(Title: Humanity Values in Minangkabau Children's Story). This article describes human values in oral stories for children from Minangkabau. This issue was raised because many traditional stories are neglected and underappreciated. The stories analyzed were 30 stories by considering the message of the story. The oral story data was obtained by recording and transcribing. Analyzing the story is done by reading it many times so that the news is received. The study results found that the story's message was to respect parents, especially mothers, the value of honesty was carried out under any conditions, to maintain a friendship in all forms of activity, and to restrain emotions in all actions. Keywords: humanitarian values, oral stories, Minangkabau children's stories, and humanitarian values.